PENDAMPINGAN ACCURATE ONLINE FITUR PEMBELIAN BAGI MUSYAWARAH GURU MATA PELAJARAN AKUNTANSI SE-KABUPATEN KUDUS - Dennyca, Dennyca Hendriyanto Nugroho; Ponny, Ponny Harsanti; Afifi, Zaenal (Jurnal Pengabdian Bukit Pengharapan, 2023)
Accurate Accounting software is able to facilitate accounting records for various types of businesses such as services, retail/trading, construction, manufacturing, restaurants, and so on. The PKM team made a field visit to the partner's location and conducted a direct interview with the chairman of the Kudus Regency Accounting Subject Teachers' Conference, asking about the condition of teachers' technological knowledge, especially regarding Accurate Online accounting software purchase features, including: problems faced by partners, offering solutions that the PKM team would provide to partner; as well as signing a partner cooperation letter. The results obtained are increased teacher resources, increased understanding of technology, and Certified Accurate Professional.